The Role of Auditing in Investor Protection - Newman, D. Paul; Patterson, Evelyn R.; Smith, J. Reed (The Accounting Review, 2005)
Protection of outside investors depends on the detection and punishment of resource diversion by corporate insiders, including managers and controlling shareholders. We focus on the role played in investor protection by self-interested auditors operating in a competitive audit market. In our setting, auditors represent the mechanism whereby detection of diversion occurs. We show that markets with relatively greater auditor penalties for audit failures and greater insider penalties for detected resource diversion have larger total investment levels, a higher proportion of the firm held by outsiders, higher audit resource investment, higher audit fees, and higher expected investment returns.